Theory and design of microwave filters - Hunter, I. C. (London, United Kingdom Institution of Engineering and Technology, 2001)
The following topics are dealt with: network theory; lumped lowpass prototype networks; circuit transformations; TEM transmission line filters; waveguide filters; and dielectric resonator filters.
Also available in print version.
Electronic reproduction.
Keywords: Microwave filters; Electronic books